Perah Oil: A Potential Substitute for Omega-3 Oils and its Chemical Properties - Tan, Nuraimi Azlan Hadi; Siddique, Bazlul Mobin; Muhamad, Ida Idayu; Salleh, Liza Md.; Hassan, Nor Diana (International Journal of Biotechnology for Wellness Industries, 2013)
The perah seed oil is a potential source for high unsaturated and omega 3 oil. It can be an alternative choice for regular vegetable oil. The chemical and physical properties need to be investigated and evaluated for it to be used feasibly in the food industries and health care products. Modern day’s faster and sophisticated instruments and techniques are used to evaluate the physicochemical properties of edible or vegetable oils. This study includes FTIR spectroscopy GC-MS and GC to evaluate the chemical properties of it while colour was used to study the physical property. The peaks by FTIR were found at 3300-3000 cm-1, 2960‐2850 cm-1, 1760‐1670 cm-1, 1650‐1580 cm-1, and 1340‐1020 cm-1. The GC-MS discover the potential beneficial compounds that available in extracted perah oil which are squalene, Vitamin E,and L.beta.-sitosterol. The GC data demonstrate about the free fatty acid profile which showed the high unsaturation in all oil samples extracted by different solvents. However, the colour measure for the visual suitable acceptability use for food or cosmetic application.